Effect of Grafting Dates on Success and Growth of Kumquat (Fortunella japonica Swingle) Sapling - Bhandari, Nirajan; Regmi, Chiranjivi (Nepalese Horticulture, 2021)
An experiment was carried out to study the effect of grafting dates on the success and growth of kumquat sapling during 2017-18 at Banepa, Kavre to standardize suitable grafting time. The experiment was conducted in a single factor completely randomized design with five treatments and three replications. The treatments consisted of five grafting dates which viz., 25th November, 10th December, 25th December, 10th January and 25th January. Scion collected from the mother plant of kumquat was grafted onto two years old trifoliate orange rootstock by side veneer method at 15 days intervals under screen house. The data were recorded at every 30 days interval and found a significant effect of grafting dates on most of the economically important parameters such as graft success percent, the mortality of sprouted grafts, sapling height, number of leaves per sapling and leaf area. The result revealed that 100% graft success was observed on the grafts prepared in January. The highest mortality (13.68±0.58%) was reported on 25th November grafted sapling. The sapling height (39.68±3.68 cm), number of leaves per sapling (23.12±3.43) and leaf area (16.34±1.05 cm2) were found superior for 10th January grafted sapling while the number of primary and secondary branches per sapling were found non-significant for all grafting dates. Therefore, the study revealed that 10th January was the most suitable time for grafting of kumquat under Kavre, Nepal conditions.